ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PADA DAERAH RAWAN KECELAKAAN DI KOTA BUKITTINGGI - Wahyu Hidayat; Arie Yulfa (JURUSAN GEOGRAFI FIS UNP, 2020)
ABTRACT Traffic accidents can occur due to the lack of availability of traffic control facilities and the lack of public awareness to comply with traffic regulations. This is a quantitative descriptive research that is focused on finding out the causing factors of a traffic accidents in Bukittinggi City including: 1). Human , 2). vehicle, 3). road f and carried out at a certain time, specifically: 1). From 07.00-08.00, 2). 12: 00-13: 00, and 3). From 16:00 to 17:00. The research sample was taken using accidental sampling technique which was further analyzed using the frequency distribution technique. The results are known that the most dominant human factor triggers an accident, while for the vehicle factor is a motorcycle.